(untitled) (VETERINARIA, 2024)
Risk of chronic clinical mastitis could be enhanced by insidious subclinical mastitis (SCM) in urban smallholder goat herds. This study was a cross-sectional survey of apparently healthy lactating Sahel does (February-March, 2023) for prevalence of SCM using California mastitis test (CMT) and bacterial culture of normal milk in Maiduguri, Nigeria. Positive CMT was graded as +1 [mild], +2 [moderate], or +3 [severe]. Standard procedures for cultural isolation and identification of bacteria were followed. Prevalence of SCM was 38% (95% CI, 26.9-52.2) from 100 does, with the parity-specific prevalence (18.7-75.0%) decreasing (p < 0.05) from 50.0% at 1st parity to 18.7% at 3rd parity and increasing (p < 0.05) to 75.0% at 6th parity. Parity was not significantly (P > 0.05) associated with the prevalence. Most of the cases (71.1%, 27/38) were mild. The CMT diagnosis was significantly (p < 0.0001) associated with bacterial isolation from the milk samples. Isolation rate was 92.1% (35/38) in SCM cases, but CMT negative milk samples had isolation rate of 4.8% (3/62). Staphylococcus spp and Streptococcus spp were isolated singly in 26.3% and 10.5% of 100 samples, respectively. Both Staphylococcus spp and Streptococcus spp were isolated together in 63.2% of the samples. Out of 34 isolates of Staphylococcus spp, 24 (70.6%) were coagulase positive. Staphylococci (89.5%, 34/38) and streptococci (73.7%, 28/38) isolation rates did not differ (χ2 = 3.118; p < 0.077). Therefore, prevalent population of SCM cases among healthy lactating Sahel goats with intramammary infections should be controlled to prevent escalation to clinical mastitis.